Growing Community Awareness and Responsibility for the Beauty and Cleanliness of the Environment in Tlasih Sidoarjo Village: Menumbuhkan Kesadaran dan Tanggung Jawab Masyarakat Terhadap Keindahan dan Kebersihan Lingkungan di Desa Tlasih Sidoarjo - Setyo Rini, Risca Retno; Rischawati, Novita; Rahmayanti, Siti Rahardhini Dwi; Supriyadi (Procedia of Social Sciences and Humanities, 2022)
Indonesia is an agricultural country. Many kinds of plants that can be grown in Indonesia. Plants are also very usefull for healing and treatment. Healing abilities and positive effects of some plants as medicine have been known long before scientists discovered various drugs with chemicals. Indonesia is rich in a variety of medicinal plants. More than 1000 species of plants can be used as raw materials for medicine, therefore the cultivation of medicinal plants in Indonesia has very good potential to be developed. In Tlasih village, on Rt.02 Rw.1, there is a group of health cadres named Asman Kencur. Asman is an acronym for Asuhan Sehat Mandiri Community whose activities include planting toga, acupressure, and making processed foods and drinks from toga plants. Asman Kencur's health cadres have a special area for planting the toga plants. But for now, the land has not been fully maintained. Therefore, we, the village service team, have provided assistance in the planting and cleaning of the toga plant.